A case report of Pancreatico Pleural Fistula presenting as recurrent right pleural effusion - Harveen Kaur; Dilbag Singh; NC Kajal; Deepak Garg (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2021)
Pancreaticopleural Fistula (PPF), is an uncommon and serious complication of chronic pancreatitis. PPF needs to be included in the differential diagnosis of recurrent and large pleural effusions especially in middle-aged men with a history of alcohol consumption. The diagnosis requires high index of suspicion, since the patients present typically with the pulmonary symptoms related to pleural effusion rather than pancreatitis. We present a case of a middle-aged male with massive recurrent right-sided pleural effusion, secondary to PPF due to chronic pancreatitis.